efertue : (4+i).(2-i)+3-i
Soluções para a tarefa
Respondido por
9
.
![(4+i).(2-i)+3-i= \\ \\ (8-4i+2i-i^2)+3-i= \\ \\ (8-2i-(-1))+3-i= \\ \\ (8-2i+1)+3-i= \\ \\ 9-2i+3-i= \\ \\ 12-3i (4+i).(2-i)+3-i= \\ \\ (8-4i+2i-i^2)+3-i= \\ \\ (8-2i-(-1))+3-i= \\ \\ (8-2i+1)+3-i= \\ \\ 9-2i+3-i= \\ \\ 12-3i](https://tex.z-dn.net/?f=%284%2Bi%29.%282-i%29%2B3-i%3D+%5C%5C++%5C%5C+%288-4i%2B2i-i%5E2%29%2B3-i%3D+%5C%5C++%5C%5C+%288-2i-%28-1%29%29%2B3-i%3D+%5C%5C++%5C%5C+%288-2i%2B1%29%2B3-i%3D+%5C%5C++%5C%5C+9-2i%2B3-i%3D+%5C%5C++%5C%5C+12-3i)
Usuário anônimo:
Valeu!
Perguntas interessantes
Física,
1 ano atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás